Implementation of Buzz Group Strategy Learning to Improve Thematic Learning Achievement Theme 2 Always Save Energy Subtheme 2 Energy Benefits in Grade Iv Students of Madrasah Ibtidaiyah Negeri 3 Jakarta Academic Year 2021/2022 - Niti Nur Afifah (International Journal Labs, 2023)
This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and refisi. The target of this study was Grade IV students . The data obtained are in the form of formative test results, observation sheets for teaching and learning activities. This research is based on the following problems: (a) Does Buzz Group learning affect thematic learning achievement Theme 2 Always Save Energy Subtheme 2 Energy Benefits in Grade IV Students? (b) How high is the level of mastery of thematic subject matter Theme 2 Always Save Energy Subtheme 2 Energy Benefits with the application of the Buzz Group learning method to Grade IV Students? . The objectives of this study are: (a) To uncover the effect of Buzz Group learning on thematic learning achievement Theme 2 Always Save Energy Subtheme 2 Energy Benefits in Grade IV Students . (b) Want to know how far the understanding and mastery of Thematic subjects Theme 2 Always Save Energy Subtheme 2 Energy Benefits after the application of Buzz Group learning to Grade IV Students . From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (58%), cycle II (72%), cycle III (100%). The conclusion of this study is that the Buzz Group method can positively affect the learning motivation of Grade IV students, and this learning model can be used as an alternative Thematic Theme 2 Always Save Energy Subtheme 2 Energy Benefits